Perancangan Media Pembelajaran Pengenalan Mikrokontroler Menggunakan Augmented Reality pada Mata Pelajaran Sistem Komputer - Ronaldo, Patrisius Jones; Wijaya, Indra; Menrisal, M (Journal of Research and Investigation in Education, 2023)
This study aims to determine the validity, practicality, and effectiveness of designing microcontroller introduction learning media in computer systems subjects. This research uses research development method (Research & Development). The research subjects were 62 students of class X TKJ SMK Negeri 2 Padang. The results of the assessment of the three validators as a whole are 83.00%, so that the level of validity can be interpreted as valid. The results of the overall practicality test assessment are 88.03%, so that the practicality level can be interpreted as Very Practical to use. The results of the overall effectiveness test assessment are 92.90%, so that the level of effectiveness can be interpreted as very effective in use.